Alkylation of benzene to cumene over mor zeolite catalysts - Vyawahare, Yogesh K.; Chumbhale, Vilas R.; Aswar, Anand S. (Revue Roumaine De Chimie, 2012)
The vapor phase alkylation of benzene to cumene (isopropyl benzene) is studied over MOR (mordenite) type zeolite at different process parameters. The reaction was also studied by adopting different methodologies (pyridine poisoning, passing of moist propylene, alkali dominant mordenite, use of coked catalyst and metal impregnated zeolite) to check the nature of product distribution and the extent of activity and selectivity to alkylated product IPB, DIPB (isopropyl benzene and diisopropyl benzene) and n-PB (n-propyl benzene). It is revealed that the adoption of different methodologies affects the activity and selectivity significantly by suppressing of alkylation / isomerisation reactions.
Keywords: Alkylation; cumene; isopropanol; MOR zeolite; propylene